(untitled) (FAVE Sección Ciencias Veterinarias, 2016)
In October 2015, a tick nymph was collected from a male Procyon cancrivorus found dead at the roadside of the National Road 119 near Mercedes city, Corrientes province, Argentina. The nymph collected was morphologically and molecularly identified as Amblyomma dubitatum and it was found infected with the alpha-proteobacterium Rickettsia bellii. To the best of our knowledge, this report constitutes the first record of the A. dubitatum - P. cancrivorus association.